Enhancement of 2000-m rowing performance after caffeine ingestion - Bruce, C. R.; Anderson, M. E.; Fraser, S. F.; Stepto, N. K.; Klein, R.; Hopkins, W. G.; Hawley, J. A. (Medicine & Science in Sports & Exercise, 2000)
PURPOSE: To investigate the effect of caffeine ingestion on short-term endurance performance in competitive rowers. METHODS: In this randomized double-blind crossover study, eight competitive oarsmen (peak oxygen uptake [VO2peak] 4.7+/-0.4 L x min(-1), mean +/- SD) performed three familiarization trials of a 2000-m rowing test on an air-braked ergometer, followed by three experimental trials at 3- to 7-d intervals, each 1 h after ingesting caffeine (6 or 9 mg x kg(-1) body mass) or placebo. Trials were preceded by a standardized warm-up (6 min at 225+/-39 W; 75+/-7.7% VO2peak). RESULTS: Urinary caffeine concentration was similar before ingestion (approximately 1 mg x L(-1)) but rose to 6.2+/-3.6 and 14.5+/-7.0 mg x L(-1) for the low and high caffeine doses, respectively. Plasma free fatty acid concentration before exercise was higher after caffeine ingestion (0.29+/-0.17 and 0.39+/-0.20 mM for 6 and 9 mg x kg(-1), respectively) than after placebo (0.13+/-0.05 mM). Respiratory exchange ratio during the warm-up was also substantially lower with caffeine (0.94+/-0.09 and 0.93+/-0.06 for the low and high dose) than with placebo (0.98+/-0.12). Subjects could not distinguish between treatments before or after the exercise test. Both doses of caffeine had a similar ergogenic effect relative to placebo: performance time decreased by a mean of 1.2% (95% likely range 0.4-1.9%); the corresponding increase in mean power was 2.7% (0.4-5.0%). Performance time showed some evidence of individual differences in the effect of caffeine (SD 0.9%; 95% likely range 1.5 to -0.9%). CONCLUSIONS: Ingestion of 6 or 9 mg x kg(-1) of caffeine produces a worthwhile enhancement of short-term endurance performance in a controlled laboratory setting.